(untitled) (Journal of Philosophy Culture and Political Science, 2022)
Abstract: The problem of self-realization of the potential of the individual has historically attracted the attention of many sciences. Of interest was the fact that the essential manifestation of potential determines the driving forces, the deep "I" of a person, his results. The solution of modern crisis social situations requires the study of the features of the manifestation of essential forces through the self-realization of the potential of the individual. The aim of the work is to consider a set of measures to ensure self-realization of the spiritual and moral potential of the individual, due to the mentality of the people of Russia. The realization of the potential of the individual is carried out in the historical space of Russian life, which creates moral restrictions for his movement. Identification and self-determination in relation to the spiritual awakens the deep essential spiritual part of the integral potential of the individual, which unfolds by the essential forces of the subject to achieve acme - the spiritual heights of self-realization. This is done in the process of movement of the individual along the stages of development - vital, sociodynamic, socio-cultural, activity, cultural and spiritual. They provide the completeness of social life, allowing the essence and strength of the spiritual and moral potential to unfold in the spiritual space, the spiritual and moral standards of culture, traditional for Russia. This is facilitated by a set of measures, including the organization of individual development of the personality, taking into account the historical, saturated with spiritual and moral values ​​of the spiritual space of Russia, the organization of the transition of the individual along the ladder of being to the higher spiritual and essential foundations of development. Keywords: spiritual and moral potential, spiritual space, spiritual and moral values, self-realization, personality, mentality, society.